Pengaruh Literasi Keuangan dan Fintech Terhadap Investasi Dengan Inklusi Keuangan Sebagai Pemediasi - Ni Putu Yuliana Ria Sawitri; Ni Nyoman Ayu Candrayani (Jurnal Ekonomi, 2025)
Rapid technology advancements and economic growth have made it simpler for consumers to get the knowledge they want.  Purposive sampling was used to choose 100 samples in total.  A survey was utilised to gather the data, and the PLS approach was used for analysis.  Three phases of analysis were used: hypothesis testing, inner model analysis, and outside model analysis. The outcomes reveal: (1) Financial literacy has a significant positive influence on investment decisions; (2) Financial technology has a significant positive influence on investment decisions; (3) Financial literacy has a significant positive influence on financial inclusion; (4) Financial technology has a significant positive influence on financial inclusion; Financial inclusion has a significant positive influence on investment decisions; (6) Financial inclusion can mediate financial literacy on investment decisions; (7) Financial inclusion can mediate financial technology on investment decisions.